Influence of money-script patterns on disordered money behaviours of young adults in Lagos - Atiri, S.O.; Akinwale, G.A.; Umukoro, O.S.; Bello, T.S. (Penerbit Universiti Kebangsaan Malaysia, 2025)
The study examined the influence of the dimensions of money script patterns on the disordered money behaviours exhibited by young adults in Lagos State to determine if money worshippers and money avoiders exhibited lower levels of disordered money behaviours than money vigilants among the participants. This study used a cross-sectional survey that involved 385 respondents. A biodata form and two psychological scales, namely, the Klontz Money Behaviour Inventory (KMBI), which assessed information on the respondent’s disordered money behaviours and the Klontz Money Script Inventory (KMSI), which measured participants’ money script patterns. One-way ANOVA analysis shows that money vigilant participants reported the highest level of disordered money behaviours (x̅=39.25) compared to money avoiders (x̅=38.63), and money worshippers reported the lowest level of disordered money behaviour (x̅=37.04). The Pearson Product-Moment Correlation result likewise demonstrates that a significant relationship existed among the dimensions of money script and disordered money behaviour, as money avoiders and money worshipers significantly exhibited disordered money behaviour compared to money vigilants. Money avoidance script correlated significantly with all the disordered money behaviour, for a correlation, r (343) = 1, positive correlation, p>0.05. Nine out of ten listed disordered money behaviours correlated with the money worship script r (343) = 0.20, p>0.05. For the money vigilant script, just seven disordered money behaviours correlated significantly with this type of money script. r (343) = 0.23, p>0.05. The study concluded that participants who are Money Avoiders and Money Worshippers often exhibited less disordered money behaviours compared to those who are Money Vigilant.